A study of early complementary feeding determinants in the Republic of Ireland based on a cross-sectional analysis of the Growing Up in Ireland infant cohort. Issue 2 (19th March 2014) - Castro, Patricia Dominguez; Kearney, John; Layte, Richard
Abstract: Objective: Early complementary feeding has been shown to increase the risk of overweight, obesity and chronic diseases later in life. Poor compliance with current guidelines on complementary feeding has been reported by Irish studies. The aim of the present paper is to identify predictors of early complementary feeding in order to help health professionals target population groups in greater need of dietary intervention as well as to provide effective advice. Design: Cross-sectional analysis of the national, longitudinal Growing Up in Ireland study. Setting: Data were derived from the first wave (2007–2008) of the Growing Up in Ireland infant cohort. Subjects: A cohort of mothers ( n 11 134) from the Republic of Ireland, interviewed when their infants were 9 months of age. Results: Of the infants, 1469 (13·5 %) had been regularly taking solids in the period between 12 and 16 weeks; this percentage increased to 47·0 % of the sample in the period between 16 and 20 weeks. Timing of formula feeding commencement, high maternal BMI and choosing a relative as the infant's minder were strongly associated with early introduction of solids both in bivariate and multivariate analysis. Those infants who started formula feeding at >4 months were 88·4% less likely to be introduced to solids early compared with those who started at <2 months (OR = 0·116; 95% CI 0·072, 0·186; P < 0·001). Conclusions: The results demonstrate that biological, social and behavioural aspects exert an important role in infant feeding practices. These findings are relevant to the design of policies and intervention programmes aimed at educating parents.